Application of EDEM Simulation for Calculating and Optimizing a Closed Coal Fly Ash Screw Conveyor - Tran, Van-Thien; Bui, Ngoc-Tam; Bui, Tuan-Anh (Applied Sciences, 2023)
In contemporary bulk material transportation systems, closed screw conveyors have become prevalent. These conveyors, enclosed within troughs or cylindrical bodies, effectively mitigate environmental contamination and material toxicity during transit. Their hermetic design prevents material dispersion by wind, thereby minimizing losses and preserving the integrity of raw materials, particularly those with potential health implications such as urea and cement. Consequently, employing a screw conveyor constitutes a prudent safety measure. Despite the widespread use of screw conveyors, a comprehensive understanding of the behavior of material particles within these systems remains elusive and subject to discrepancies across various methodologies. Presently, a multitude of calculation methods and applications exist, resulting in disparities between theoretical computations and practical implementation. Drawing upon Alan W. Roberts’ meticulously devised calculation methodology, renowned for its precision, the authors have developed a swift computational tool utilizing VBA Excel software 2023. Additionally, EDEM simulation software was employed to model granular material behavior. The ensuing calculations guided the selection of optimized technical dimensions for the screw conveyor, which were then fabricated and subjected to real-world testing at the Vinh Tan thermal power plant. Remarkably, the achieved output capacity demonstrated a mere 7% deviation from calculations performed with the VBA program and a 2% variation from those conducted via EDEM simulation. Furthermore, a comprehensive graph depicting the relationship between screw conveyor speed and capacity has been provided, affording a means to finely tune throughput with exceptional accuracy along the production line. The results obtained provide the basis for the development of a device that meets the required capacity specifications accurately and precisely on the first attempt. This accomplishment satisfies stringent capacity standards without the need for any adjustments or modifications, all while ensuring minimal cost and time efficiency.